2020
DOI: 10.1200/po.19.00281
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of an Amplicon-Based Liquid Biopsy for DetectingALKandROS1Fusion and Resistance Mutations in Patients With Non–Small-Cell Lung Cancer

Abstract: PURPOSE Liquid biopsy specimen genomic profiling is integrated in non–small-cell lung cancer (NSCLC) guidelines; however, data on the clinical relevance for ALK /ROS1 alterations are scarce. We evaluated the clinical utility of a targeted amplicon-based assay in a large prospective cohort of patients with ALK/ROS1-positive NSCLC and its impact on outcomes. PATIENTS AND METHODS Patients with advanced ALK/ROS1-positive NSCLC were prospectively enrolled in the study by researchers at eight French institutions. Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…In February 2018, a 62-year-old woman with a previous light smoking history (five packs/year) was diagnosed with lung adenocarcinoma with pleural, pericardial, lymph nodal and bone metastases. After two cycles of first-line chemotherapy with cisplatin and pemetrexed (best response stable disease) and the detection of an EZR-ROS1 fusion on liquid biopsy (InVisionFirst-Lung amplicon-based assay), 6 confirmed by FISH on tumor sample, the patient received entrectinib 600 mg daily since July 2018. No relevant side effects were recorded and partial response was achieved after two months.…”
Section: Case Presentationmentioning
confidence: 99%
“…In February 2018, a 62-year-old woman with a previous light smoking history (five packs/year) was diagnosed with lung adenocarcinoma with pleural, pericardial, lymph nodal and bone metastases. After two cycles of first-line chemotherapy with cisplatin and pemetrexed (best response stable disease) and the detection of an EZR-ROS1 fusion on liquid biopsy (InVisionFirst-Lung amplicon-based assay), 6 confirmed by FISH on tumor sample, the patient received entrectinib 600 mg daily since July 2018. No relevant side effects were recorded and partial response was achieved after two months.…”
Section: Case Presentationmentioning
confidence: 99%
“…The ROS1 p. G2032R resistance mutation was found in 30% of evaluated cases. Patients with no detectable mutations in ctDNA had a longer median overall survival despite progression on TKIs [ 63 ].…”
Section: Available Assays and Target Genomic Alterations In Lung Cmentioning
confidence: 99%
“…While the detection from tissue samples is routinely implemented as a gold standard, liquid biopsies are not well established and are challenging in this setting (8). Importantly, recent reports et al reported a sensitivity of 67% at baseline, 46% at progression, and 11% under treatment, respectively for ALK and ROS1 rearrangements using the InVisionFirst-Lung NGS assay (Inivata, Morrisville, NC-USA) for plasma testing and a combination of FISH, IHC, and NGS for tissue testing (13). Interestingly and in line with the results reported in this study, a higher detection rate was observed in patients at progression than those under active anti-ALK treatment, suggesting that longitudinal tracking of ALK rearrangements under treatment might be predictive of response to therapy.…”
Section: Discussionmentioning
confidence: 99%